Augmented immunogenicity of the HPV16 DNA vaccine via dual adjuvant approach: integration of CpG ODN into plasmid backbone and co-administration with IL-28B gene adjuvant - Yan Zhou; Ting Zhang; Zhirong Wang; Xuemei Xu (Virology Journal)
Abstract Therapeutic human papillomavirus (HPV) DNA vaccine is an attractive option to control existed HPV infection and related lesions. The two early viral oncoproteins, E6 and E7, are continuously expressed in most HPV-related pre- and cancerous cells, and are ideal targets for therapeutic vaccines. We have previously developed an HPV 16 DNA vaccine encoding a modified E7/HSP70 (mE7/HSP70) fusion protein, which demonstrated significant antitumor effects in murine models. In this study, we employed multifaceted approach to enhance the potency of the HPV16 DNA vaccine. Strategies including inserting CpG oligodeoxynucleotide (CpG ODNs) into the vaccine vector backbone, selecting cytokine gene adjuvants, combining plasmids encoding mE6/HSP70 and mE7/HSP70, and utilizing electroporation for vaccination. Our findings revealed that mice immunized with CpG-modified vaccines, coupled with an IL-28B gene adjuvant exhibited heightened antigen-specific CD8+ T cell responses. Additionally, the combination of mE6/HSP70 and mE7/HSP70 plasmids synergistically enhanced the specific CD8+ T cell response. Furthermore, vaccination with CpG-modified mE7/HSP70 and mE6/HSP70 plasmids, alongside the Interleukin-28B (IL-28B) gene adjuvant, generated substantial preventive and therapeutic antitumor effects against HPV E6- and E7-expressing tumors in C57BL/6 mice. These results suggested that integrating these multiple strategies into an HPV DNA vaccine holds promise for effectively controlling HPV infection and related diseases.